Influence of technical variables on the victory rates in the 2021 Brazilian National Futsal League - de Andrade Santos, W. S.; Aidar, F. J.; Da Cunha Voser, R.; Brito, C. J.; Dos Sanos, J. L.; Getirana-Mota, M.; De Mendonça, J. O. S.; Rosa, J. L.; Pinto, P. R. S.; Freitas Junior, A. P. A.; De Oliveira, D. C. X.; Vieira-Souza, L. M. (Journal of Physical Education and Sport, 2023)
Futsal is one of the most popular sports in the world, with Brazil being the birthplace of the sport and home to one of the most successful teams and competitive leagues between clubs within the countries. To that end, analyzing the data provided by both game moments and match results is critical to qualify and improve the sport`s technical and tactical dynamics. Its intermittent characteristic, presenting varying moments of control and extreme excitement and the possibility of infinite athlete changes, allow structural changes in team formations during the match. This study investigates the impact of the goals, shots, tackles, and assists averages, and right and wrong passes on team victory indices. Furthermore, it quantitatively and descriptively evaluates 154 matches in the qualifying phase of the 2021 Brazilian National Futsal League in which 23 teams competed. The league`s official scout collected the data. A descriptive analysis was employed first, followed by a Spearman correlation. When observing the correlations analyzed, a positive and strong correlation was identified between the variables Average Goals/Victory (r = 0.82), Average Help/Victory (r = 0.60), and Average Kicks/Victory (r = 0.60). However, this analysis showed no correlation in the right passes (r = 0.22) and wrong passes (r = 0.08) concerning the victory rates. Thus, we can infer that the teams that have better goal, assist, and kick averages tend to obtain a higher number of victories.